Análisis de un enterramiento con cubierta ›entelado‹ de época altoimperial en Augusta Emerita (Mérida, Badajoz) - Bustamante-Álvarez, Macarena; Picado Pérez, Yolanda; Vicente Palomino, Sofía; Yusá Marco, Dolores Julia; Madrid García, José Antonio (Madrider Mitteilungen, 2020)
We present a grave dated in the Early Roman Empire times with remains of textiles adhered on its cover. It was located in Augusta Emerita (current Mérida). We carry out an archaeological and contextual study of the tomb as well as a research of the materials located in its deposit. In addition we have made a series of archaeometric analyzes that allow us to know the nature of the fabric used and to present an approach of the praxis of this curious practice.